PENGARUH KEBIJAKAN PIMPINAN, SINISME DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA PEGAWAI PANGKALAN UTAMA TNI ANGKATAN LAUT XIII TARAKAN KALIMANTAN UTARA - Akhbar Faisal Harahap; Rini Megasari Nasution; Rosnanni Pasaribu; Mahyun .; Marni Irawati (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
The Formulation of this research is how the leader of the policy of leadership, cynicism and quality of working life on the performance of The Main Officer Of The Navy XIII Tarakan in North Kalimantan, and the purpose of this research is to know and analyze the policy of leadership, cynicism and quality of work life on the performance of The Main Base Officers Of The Navy XIII Tarakan North Kalimantan . This research is a quantitative descriptive study. Data collection techniques are conducted through interviews, inquiry lists and documentation studies. The samples in this study were as many as 96 employees. Variables are measured at Likert scale. Hypothesis testing using multiple linear regression analyses through F-test and T-Test. The Results of the test in unison showed that the policy of leadership, cynicism and the quality of work life showed a very noticeable influence on the performance of the employee performance of the Navy XIII Tarakan North Kalimantan with a value of Fcount 37,914 Ftable 2.70 and significance value of 0.000b. Adjusted number of R Square by 0. 538 or (53.8%) indicates that the percentage of contributions influenced by independent variables (leadership policy, cynicism and quality of work life) on dependent variables (employee performance) of 53.8%. Partially, the leadership policy has a positive effect on the employee performance of The Navy XIII Tarakan North Kalimantan with a value of tcount ttable (6,447 1,984) and a significance value of 0. 000. Cynicism has a negative and insignificant effect on the employee performance of The Navy XIII Tarakan North Kalimantan with a value of tcount ttable (-5,315 1,984) and a significance value of 0. 000. The quality of working life has a positive and significant impact on employee performance of The Navy XIII Tarakan North Kalimantan with a value of tcount ttable (6,100 1,984) and a significance value of 0. 000. The highest value of a regression coefficient is leadership policy (X1) of 0. 467 or 46.7% and is the most dominant variable affecting the performance of the main base officer of The Navy XIII Tarakan North Kalimantan.